Disseminated Infection Caused by Eggerthella lenta in a Previously Healthy Young Man: A Case Report. (17th December 2012) - Salameh, Ahmad; Klotz, Stephen A.; Zangeneh, Tirdad T.
Abstract : Anaerobic bacteria are the predominant normal flora of the mucous membranes which may cause life-threatening disseminated infections and are often difficult to culture from infected sites. Eggerthella (previously known as Eubacteria species) is an anaerobic, nonsporulating, nonmotile, Gram-positive rod that is found in the human colon and feces and has been isolated from various other clinical specimens. We report a case of complicated disseminated anaerobic bacterial infection with Eggerthella lenta in a healthy immunocompetent man causing multiple brain abscesses, liver abscesses, necrotizing pneumonia, and osteomyelitis of the left radial bone. He was successfully treated with empiric penicillin G and metronidazole.